Dry deposition of ammonia in a coastal dune area: Measurements and modeling. (1st April 2023) - Vendel, K.J.A.; Wichink Kruit, R.J.; Blom, M.; van den Bulk, P.; van Egmond, B.; Frumau, A.; Rutledge-Jonker, S.; Hensen, A.; van Zanten, M.C.
Abstract: Ammonia deposition is a threat to many natural ecosystems, including coastal dune areas, because of eutrophication and acidification. Direct measurements of ammonia fluxes are nevertheless scarce. In this paper we present a full year of measurements to derive the ammonia dry deposition flux in a Dutch coastal dune ecosystem, based on the aerodynamic flux-gradient method (AGM). We found a mean ammonia flux of −7.1 ± 1.7 ng m −2 s −1, and an annual ammonia deposition flux of −132 ± 32 mol ha −1 yr −1 (equivalent to 1.8 ± 0.4 kg N ha −1 yr −1 ), which is at the low end of the range from estimates from literature made with inferential methods. Modeling the fluxes with the DEPAC module resulted in a mean flux of −17.0 ng m −2 s −1 . The model overestimated the deposition fluxes, but diurnal variations of the fluxes derived from measurements were well captured by the model. We propose to change certain DEPAC parameters, like the leaf area index, to values more applicable for a dune ecosystem and show that this improves the agreement between model and measurements. Highlights: Dry deposition fluxes of ammonia were measured in a Dutch coastal dune area. Half-hourly data were collected for a full year with a wet denuder instrument. Fluxes from the aerodynamic flux-gradient method were compared with modeling. Modeled fluxes captured measured diurnal variations, but overestimated deposition. Modeled fluxes were sensitive to leaf area index and compensation points.